Resolution of cystoid macular edema with topical carbonic anhydrase inhibitor in a patient with retinal dystrophy associated with Cohen syndrome - SEVİK, MEHMET ORKUN; ŞAHİN, ÖZLEM (TAYLOR & FRANCIS INC, 2021)
Background: Cohen Syndrome (CS) is an autosomal recessive multisystemic disorder characterized by various ophthalmologic findings, including retinal dystrophy and associated cystoid macular edema (CME), in which there was no known effective treatment approach. Material and Methods: We describe a CS patient with a homozygous c.62 T > G, p.(Leu21*) mutation in the VPS13B gene with a topical carbonic anhydrase inhibitor (CAI; brinzolamide %1, thrice daily) responding CME. Case Description: A seven-year-old girl with an established diagnosis of CS was referred with a primary complaint of nyctalopia. On ophthalmologic examination, bilateral decreased visual acuity and normal-appearing macula with mild optic disc pallor were present. However, the detailed evaluation revealed bilateral blunted foveal reflexes, barely visible foveal pigmentation, and slightly attenuated retinal vessels without any peripheral retinal pigmentary changes in dilated fundus examination, and CME on optical coherence tomography. Bilateral topical brinzolamide thrice daily was initiated for CME. Visual acuity increased, and CME was resolved except for minimal schisis at the inner nuclear layer level at the third-month follow-up visit and remained stable up to one-year follow-up. CME reappeared after five months of self-discontinuation of the patient's therapy but resolved again with treatment resumption. Conclusion: We report the first case of CME secondary to rod-cone dystrophy associated with CS showing improvement in anatomy and visual acuity with a topical CAI.
Keywords: Cohen syndrome; cystoid macular edema; CME; carbonic anhydrase inhibitor; CAI; brinzolamide; ISCEV STANDARD